A-05 Self-Reported Symptomatology in Athletes with Autism Diagnosis. (18th June 2020) - Bennett, R; Horne, K; Datoc, A; McDonald, B; Lashley, L
Abstract: Objective: To examine the relationship between athletes with and without Autism diagnosis and self-reported symptoms as measured by ImPACT. Method: Participants were selected from an archival de-identified sports medicine ImPACT database. The sample (N = 232) was primarily male (72.4%) student athletes with a mean age of 15.41 years (SD = 1.292). Participants were divided into two groups: Autism diagnosis (n = 130); No diagnosis (n = 102). An independent samples t-test was conducted to analyze the variation of self-reported symptoms between athletes with and without an Autism diagnosis. Results: The independent samples t-test revealed significant differences between diagnostic groups and self-reported cognitive (t = 5.832, p < .001, d = .72); sleep (t = 4.040, p < .001, d = .51); vestibular somatic (t = 4.154, p < .001, d = .53); and affective symptomatology (t = 3.988, p < .001, d = .51). Athletes with a diagnosis of Autism reported more symptoms overall in comparison to athletes without a diagnosis. Conclusions: These findings suggest that prior psychological diagnoses play a significant role in symptom scores; however, the degree to which these symptoms can be attributed to the diagnosis itself or the concussion is unknown. It should be noted that individuals who have been diagnosed with Autism may already be at an increased risk of sleep difficulties, emotional regulation, and sensory stimulation within the environment. Therefore, differentiating the symptom scores from preexisting symptoms of Autism from a concussion can be beneficial when helping athletes return to play.